The Fracture Mechanics of Plant Materials Wood and Bamboo - Shao, Zhuoping (Springer Singapore, 2018)
This book introduces readers to the application of fracture mechanics and mesomechanics to the analysis of the fracture behaviors of wood and bamboo. It presents a range of research methods to study the fracture behaviors of wood and bamboo, taking into account their various fracture mechanisms resulting from differences in their macroscopic and microscopic structures. It combines theoretical analysis with experiments, as well as various mathematical tools and experimental approaches. The research methods are illustrated by simple schematic diagrams, and the results obtained are largely presented as tables and figures, helping to make the book concise and compact. As such, it provides a valuable guide to the development of new biocomposites that possess exceptional strength and toughness properties and successfully overcome the shortcomings of biomaterials.